Relationship between Entrepreneurial Intention Among Undergraduates Student and Entrepreneurship Education: Differences between Gender - Buddi Wibowo (APMBA (Asia Pacific Management and Business Application), 2016)
Entrepreneurial intentions among undergraduates students need more indepth study to reveal entrepreneurial intention formation model, intention determinant variables, and how those variables interact each other in  the intention formation process and intention strength level. Personal attitudes and social norms are the most important variable influencing entrepreneurial intentions, besides perceived behavioral control. These three variables are the most important entrepreneurial intentions determinant variable  that each are directly influenced by personal beliefs. Prior research show gender gaps in entrepreneurial activity and there is a significant different entrepreneurial intentions formation process between gender. Entrepreneurship educations are aimed to change all personal beliefs to be more positive to entrepreneurial activity so we could find strong entrepreneurial intentions  among undergraduate students. Empirical test show that entrepreneurship education significantly influence personal attitude dan perceived behavior control to be more favorable in developing entrepreneurship education. Female students tend to value more on non monetary entrepreneurial benefits than male student. Entrepreneurship education strengthen each gender’ tendency to value more what they initially believe.